CAD/CAM application in manufacturing / Salwa Mohd Sayutti and Siti Jasmeen Mohd Hashim - Mohd Sayutti, Salwa; Mohd Hashim, Siti Jasmeen (1996)
The first chapter is more about the basic definition of several terms that will be use in the following chapter. The basic terms that we use are CAD, CAM, CNC where they are related to each other. The explanations will give a brief idea on what it is all about. The second chapter is about the project itself. It consists of the introduction to the project and the applications of CAD/CAM in manufacturing and for this case cable clamp has been chosen. CAD/CAM Software will be use to create the surface, generate a tool path and generate the NC program for the profile of a die insert of a cable clamp. The third chapter is more on the drawing of product and the programming. We used Autocad Release 12 for product drawing where this is one of the CAD softwares. It gives a brief explanation on the machining and manufacturing process in producing cable clamp. To produce an actual cable clamp, it used a pressure die casting process. The fourth chapter is briefly about die, the definition and the manufacturing process. Chapter 3 and chapter 4 are important to give a rough idea on this project. The fifth chapter is the real usage on CAD software that is Autocad and Autosurf. On this chapter we select the system used, the profile drawing of a die insert and also the programs use to generate the drawing.